(untitled) (Revista de Biología Marina y Oceanografía, 2024)
A study was designed with the purpose of preliminarily evaluating heavy metal removal capacity of the green microalga Auxenochlorella sp., exposing it to different concentrations of copper in synthetic solutions. The study was carried out in the laboratory of Aguamarina Spa Company. Auxenochlorella sp. microalgae. were kept under cryopreservation at -80 °C until the date of the experiment. Then they were thawed and reactivated to be maintained in the culture medium described by the supplying laboratory. The microalgae were transferred from the cryogenizer tube to a test tube and then to Erlenmeyer flasks where they were maintained under controlled conditions of temperature (19 °C), aeration and a photoperiod of 24:0 h of light. Three concentrations of copper were used in the experiment; 1.0, 3.0 and 5.0 mg L-1, respectively, each in triplicate and two additional controls, C1 contained only the microalgae without culture medium and C2 contained the microalgae with culture medium, with an initial concentration in all treatments of 3.87·106 cells mL-1. Finally, the results obtained allow us to conclude that the microalga Auxenochlorella sp. exposed to copper at different concentrations was able to remove up to 15.32% of copper. The concentrations of the metal were not sufficient to cause growth inhibition or mortality, however, the copper removal rates were not close to what was expected for this taxonomic family of microalgae. According to the results, this problem must continue to be addressed, in order to find optimal environmental and nutritional factors that improve the efficiency of copper removal by the microalga Auxenochlorella sp.